An In Vitro Method for Studying the Three-Way Interaction between Soybean, Rhizophagus irregularis and the Soil-Borne Pathogen Fusarium virguliforme - Giachero, María L.; Marquez, Nathalie; Gallou, Adrien; Luna, Celina M.; Declerck, Stéphane; Ducasse, Daniel A. (Frontiers in Plant Science, 2017)
In this work, we described an in vitro system adequate for investigating the pathosystem soybean/arbuscular mycorrhizal fungi (AMF)/Fusarium virguliforme. Pre-mycorrhized plantlets with Rhizophagus irregularis were infected by F. virguliforme either locally via a plug of gel supporting mycelium (Method 1) or via a macroconidia suspension applied to the medium surface (Method 2). Root colonization by the AMF and infection by the pathogen were similar to the usual observations in pot experiments. Within a period of 18 days, more than 20% of the roots were colonized by the AMF and infection by the pathogen was observed in all the plants. In presence of AMF, a decrease in symptoms and in the level of root tissue infection was noticed. With Method 1, smaller necrotic lesions were observed in the pre-mycorrhized plantlets. In Method 2, pathogen infection was slower but more homogenous. These results demonstrated the suitability of the in vitro cultivation system to study the pathosystem soybean/AMF/F. virguliforme. We propose this in vitro cultivation system for studying the mechanisms involved in the biocontrol conferred by AMF against F. virguliforme in soybean.